Editorial: Children’s Voices on Privacy Management and Data Responsibilization - De Wolf, Ralf (2020)
Contemporary children live in datafied societies in which they navigate and use technological innovations that drive on their personal information. Instructing privacy literacy is often presented as a key solution to help children manage their personal data responsibly. While there is agreement on the empowering potential of privacy literacy for children, there are also concerns over the burden that this responsibility places on them and their capacity for resilience. Children are key stakeholders in this debate. Nonetheless, we rarely hear their voices on issues related to their online privacy and data responsibilization. The articles included in this thematic issue account for this limitation by amplifying the voices of children, looking into the practices of parents and exploring the role of the tools being used.